Analyzing watermarking color image channels with wavelet and Schur decomposition technique - Jasim Abdullah, Maryam; Ismail, Amelia Ritahani; Ibrahim, Adamu Abubakar (IEEE, 2025)
This study explores a digital watermarking technique that integrates frequency domain transformation with Schur Decomposition to enhance both imperceptibility and robustness in grayscale and color images. While grayscale images are represented by a single channel, color images use three distinct channels (RGB), offering different opportunities for watermark embedding. The proposed algorithm applies Discrete Wavelet Transform (DWT) combined with Schur Decomposition across individual RGB channels. Experimental evaluations on three color images reveal that embedding the watermark in the red channel offers superior robustness, particularly under noise attacks. Compared to existing methods, the proposed technique achieves an average PSNR of 69.59 dB and sustains high Normalized Cross-Correlation (NCC) values under various distortions. These findings highlight the method’s effectiveness in achieving an optimal balance between imperceptibility and robustness in digital watermarking applications.